The effectiveness of compatible agrophytocenoses depending on the allelopathic interaction of plants - Семенченко, Олена Леонідівна; Semenchenko, Olena; Мельник, А.В.; Melnyk, A.; Заверталюк, Володимир Філімонович; Zavertalyuk, Volodimir; Заверталюк, А.В.; Zavertalyuk, А.; Пастухов, В.І.; Pastukhov, V.; Киріченко, Р.В.; Kyrychenko, R. (Мелітопольский державний педагогічний університет ім. Богдана Хмельницкого, 2020)
The main criteria for the functioning of agronomic phytocoenosis are indicators of their economic and energy efficiency. In particular, the issues of manufacturability and rational use of sown areas during the growing season characterize the level of agronomic culture in a particular geographical area. Under these conditions, it is important to study the possibility of joint cultivation of agricultural plants, which will reduce energy consumption, improve the phytosanitary condition of crops and increase the profitability of agricultural production. When growing tomatoes in compatible crops, it is necessary to take into account not only aspects of technology, but also the interaction of plants with each other at the level of physiological and biochemical processes. That is why allelopathic relationship between plants, due to the physiologically active substances they secrete at the initial stage of ontogenesis, is not without the interest. It is the scientific basis for the development of sound crop rotation and mixed (compacted) crops, and also helps to increase the productivity of agro- and natural coenoses in order to prevent soil fatigue in monoculture, control weeds, pests, phytopathogenic organisms, etc. Основними критеріями функціонування агрономічного фітоценозу є показники їх економічної та енергетичної ефективності. Зокрема, питання технологічності та раціонального використання посівних площ протягом вегетаційного періоду характеризують рівень агрономічної культури в певний географічний район. За цих умов важливо вивчити можливість спільного вирощування сільськогосподарських рослин, що зменшить енергоспоживання, покращить фітосанітарний стан сільськогосподарських культур та збільшить рентабельність сільського господарства виробництво. Вирощуючи помідори в сумісних культурах, слід враховувати не тільки аспекти технології, але і взаємодія рослин між собою на рівні фізіологічних та біохімічних процесів. Ось чому алелопатичні стосунки між рослинами через фізіологічно активні речовини, які вони виділяють на початковій стадії онтогенезу, не без інтересу. Це наукова основа розвитку міцного сівозміни та змішаних (ущільнених) культур, а також сприяє збільшенню продуктивність агро- та природних ценозів з метою запобігання втоми ґрунту в монокультурі, боротьби з бур’янами, шкідниками, фітопатогенними організми тощо.
Ефективність сумісних агрофітоценозів залежно про алелопатичну взаємодію рослин
Keywords: сумісні культури; сompatible crops; помідор; tomato; алелопатія; allelopathy; лук-шалот; shallots; cолодка кукурудза; sweet corn